The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/erv.2562
|View full text |Cite
|
Sign up to set email alerts
|

Family Functioning and Relationship Quality for Adolescents in Family‐based Treatment with Severe Anorexia Nervosa Compared with Non‐clinical Adolescents

Abstract: This longitudinal study explored family functioning and relationship quality for adolescents with severe anorexia nervosa (AN). An important outcome given healthy family functioning supports effective adolescent development. Fifty-four female adolescents and their parents, treated with family-based treatment after inpatient admission, and 49 non-clinical age-matched adolescents and their parents were compared at assessment and 6 months after session 20. At baseline, AN group mothers and fathers reported poorer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 46 publications
1
15
0
1
Order By: Relevance
“…The results can further aid the development of interventions aimed at supporting caregivers. In future studies, it is important to carefully monitor how each parent/caregiver responds to and copes with treatment (Wallis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The results can further aid the development of interventions aimed at supporting caregivers. In future studies, it is important to carefully monitor how each parent/caregiver responds to and copes with treatment (Wallis et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Using self-report measures of attachment, significant differences in attachment were found by Batista et al (2018), who used the Experiences in Close Relationships-Revised (Fraley et al, 2000) in a sample of 35 adolescents with AN and 35 Healthy Control (HC) adolescents. By contrast, Wallis et al (2018), who used a brief version of the IPPA , did not find any differences between their AN sample (n = 54) and HC sample (n = 49), either at baselinewhen the AN group were starting FBTor 14 months later, when the two samples again completed the IPPA. The 14-month follow-up represents 6 months after the end of treatment, which was 20 sessions of FBT.…”
Section: Studies Of Attachment In Adolescent Eating Disorder Samplesmentioning
confidence: 81%
“…Knowing the importance of communication for the development of healthy bonds, such problems in relating to other people can, at least in part, be understood in the light of the findings of Wallis et al (2018), who identified difficulties in interpersonal communication of fathers. In the same perspective, Treasure et al (2019) draw attention to the fact that fathers recognize that improving communication skills could be a useful and valuable tool, both for the relationship with their daughters and for the relationship with others in general.…”
Section: Resultsmentioning
confidence: 99%
“…The analyzed literature also indicates the need for support and strengthening of fathers in the face of a complex condition such as EDs. In this sense, Wallis et al (2018) expose the fathers' difficulty in dealing with the impact of the development process of daughters with AN and suggest that strengthening the support provided by health professionals to these fatherss may be important. In the same perspective, Korotana et al (2018) emphasize the importance of making efforts to provide support and strengthen the relationship between the father and the daughter being treated for ED.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation